Out-of-Plane bending behavior of a novel double steel plate concrete Composite-New tubular roof structure - Liang Yue; Yue Yang; Yi-Ran Liang; Li-Yan Xu; Jie Xu; Chen Wang (Tunnelling and Underground Space Technology, 2026)

Spatial patterns and environmental determinants of topsoil charcoal across altitudinal gradients in the western Tianshan Mountains, Northwest China - Yi Ran; Jianyong Li; Ninglian Wang; Yaqi Liu; Shuqiang Pei (Review of Palaeobotany and Palynology, 2026)

Bacterial surface interfaces in food systems: a programmable regulatory layer - Hao-Ran Zhang; Jun Meng; Yun-Peng Hao; Jing-Qian Song; Xiao-Yue Wang; Jing-Yi Yang; Zai-Chen Li; Jun Xi; Chang-He Ding; Tong Li (Trends in Food Science & Technology, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Methanogenic community and pathway responses to iron addition in high-load chicken manure anaerobic digestion under ammonia stress - Jiang Li; Ya Tang; Yi Ran (Waste Management, 2026)

Cyanidin chloride activates mitophagy to delay aging via PINK1/parkin pathway - Zhaotun Hu; Yan Ran; Xiaocong Li; He Zha; Yi Xiao (Food Research International, 2026)

PFDA exposure promotes myocardial aging and fibrosis via hyperactivation of the MTORC1 signaling axis - Xiao Guang Chen; Ze Yu Liao; Yi Zhang; Ran Li (Food and Chemical Toxicology, 2026)

A bubble-propelled microneedle patch with photothermal-controlled NO release for eradicating biofilms in diabetic wounds - Xiaojuan Zhao; Yi Li; Zhichao Ran; Peihang Song; Junpei Mei; Wenwei Liu; Chaoqun Liu; Ningning Song; Yanwei Yang (Chemical Engineering Journal, 2026)

Three-dimensional level set-based topology optimization using the adjoint method for a tee flow equalizer with a low-pressure-loss uniform air supply - Yan Tian; Ran Gao; Yi Wang; Angui Li; Xinpeng Hao; Hui Guo; Liwei Tian (Building and Environment, 2026)

Decoupling of abundance and activity: Low-abundance comammox contributes substantially to ammonia oxidation in N-fertilized paddy soils - Yi-Xuan Zhang; Wen-Jing Qin; Ran Jiang; Peng Li; Man-Young Jung; Sheng Zhou; Zhe-Xue Quan (Applied Soil Ecology, 2026)

Multiplexed EDL-FET biosensor with tannic acid stabilization for simultaneous p-Tau217 and Aβ42/Aβ40 detection in plasma and whole blood from stroke patients - Shang-Chi Chien; I-Yin Chang; Yong-Chuan Chen; Yi-Zhen Lai; Yu-Fang Chen; Pei-Lun Sun; Bor-Ran Li; Yu-Lin Wang; Jung-Chih Chen (Analytica Chimica Acta, 2026)

A chemical-free approach for effective abatement of acetochlor in drinking water - Xinyuan Yi; Yue Du; Zhixuan Tan; Wanxin Li; Ran Yin (Journal of Hazardous Materials, 2026)

Outdoor light at night, sleep disorder, and atopic diseases among children and adolescents: a cross-sectional study - Si-Han Wu; Le-Bing Wang; Xiao-Fan Lu; Yang-Yang Li; Joachim Heinrich; Lidia Morawska; Steve Hung Lam Yim; Shao Lin; Bin Jalaludin; Yi-Ran Chen; Xiao-Yi Liu; Yuan-Yuan Fan; et al. (International Journal of Hygiene and Environmental Health, 2026)

Soy milk fermented by Bacillus subtilis SP-8-5 and Lactiplantibacillus plantarum 4_3 exhibits sedative-hypnotic ability in vivo - Zhen Liu; Zhao-Ying Zeng; Yu-Jin Li; Bin Zhou; Shi-Yi Sun; Xia Ou; Hua Qi; Chen-Jian Liu; Xiao-Ran Li (Food Research International, 2026)

Residential greenness and incident type 2 diabetes: A large prospective cohort study in China integrating evidence from 17 global cohorts - Jian-Cheng Jiang; Chuan-Jiang He; Ai-Min Xu; Lu Wang; Xiao-Qi Zhu; Bei-Bei Li; Wen Liu; Ya Qiu; Jing-Ran Xu; Min-Hui Li; Zhuo-Hao Wang; Xiao-Guang Zou; et al. (Environmental Research, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

MCM-41 induced NiCe synergistic constructs Ni-OV-Ce interface for enhanced oxygen transfer in dry methane reforming - Yuanjing Ran; Xing Yi; Daoping Ye; Tao Zhang; Li Lv; Wenxiang Tang; Yan Wang; Zongpeng Zou; Shengwei Tang (Chemical Engineering Journal, 2026)

Dual-enhancement strategy for high-performance multimodal hydrogel sensors in deep learning-assisted speech recognition systems - Xiang Di; Liqi Li; Yi Wang; Weiqiang Ran; Zihan Chen; Yaning Feng; Bo Yu; Jiawen Hou; Di Chen; Chungang Yuan (Chemical Engineering Journal, 2026)

Regulation mechanism of N2O and CH4 emissions during the pig manure composting amended with Polygonum Multiflorum Thunb - Ya-jun Duan; Hong-sheng Wu; Jiang-yu Yang; Zheng-tong Zhou; Tao-ran Shi; Cheng Cheng; Zhen-wei Li; Chun-fa Wu; Ming-chun Di; Yu-dong He; Feng-yi Hu (World Journal of Microbiology and Biotechnology, 2026)

Galectin-3 in systemic lupus erythematosus: a meta-analysis - Yang Wu; Li-Na Jiang; Jing-Ru Wu; Yi-Ran Lu; Ting-ting Lu; Ji-Min Zhu; Jing Li; Shanshan Xu; Bai-Kun Li; Cheng-Gui Miao; Yan-Mei Mao (Immunologic Research, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

A degradable, highly tough, and resilient nanocomposite hydrogel for self-powered wearable sensors and a deep learning-assisted recognition system - Xiang Di; Weiqiang Ran; Yi Wang; Ruotong Zhang; Bo Yu; Baohui Li; Jiawen Hou; Chungang Yuan (Chemical Engineering Journal, 2026)

A genetic clash of sister groups: first-ever intergeneric and interspecific mitogenome comparisons between two close gall midge genera (Cecidomyiidae: Cecidomyiinae: Cecidomyiini): the floral and veggie-versatile Contarinia and the mango-mad Procontarinia, with phylogenetic applications - Xiu-Fang Dong; Yi-Fan Zhang; Xu-Yuan Gao; Ning-Bo Ma; Yu Ji; Yan-Fei Li; Yi-Ran Mu; Zheng-Hao Yue; De-Wei Wei; Yong-Hao Yu; Hai-Li Qiao; Wen-Jun Bu; et al. (Arthropod-Plant Interactions, 2026)

Deep learning and hyperspectral imaging for non-destructive amino acid detection in live carp fillets - Ying-jie Qi; Yi-Ming Cao; Yan Zhang; Qi Wang; Ran Zhao; Kai-Kuo Wang; Ying-Jie Chen; Xia-Jun Qi; Jiong-Tang Li (Food Research International, 2026)

Decoding the dynamic formation of bolus: A multimodal fusion and simulation framework for texture perception-regulated oral processing - Che Shen; Xinyu Jiang; Lizhang Wu; Zidong Chen; Zihao Li; Ran Wang; Wenxi Qi; Yi Zhang; Xinying Zhou; Bo Wang; Kezhou Cai; Baocai Xu (Food Research International, 2026)

Size-dependent lipidomics and fatty acid profiles of fat globules in buffalo milk - Shaohong Jin; Jinsu Liao; Yanan Sun; Ran Wang; Ling Li; Lianqiao Wu; Jianhuan Wei; Pengjie Wang; Fazheng Ren; Yi Wang (Food Chemistry, 2026)

Cellular copper overload mediates senescence-associated secretory phenotype induction in BV2 microglia following lead and copper exposure - Tao Wang; Chao Chen; Ran Li; Li-Hong Su; Hao-Jie Tian; Hui-Jing Wang; Jia-Yi Xiong; Qing Dai; Di Wu; Gang Zheng (Food and Chemical Toxicology, 2026)

The effect of high-pressure homogenization pressure on the 3D printing of potato protein secondary emulsion - Yi Liu; Hao-ran Chen; Ao-xue Qie; Chong-hao Bi; Zhi-gang Huang; Quan-lai Li; Qiu-yue Du (Food and Bioproducts Processing, 2026)

Investigation on the High Food Availability Zone in riparian areas: From the perspective of fish food supply - Xiangdong Pan; Shuang Ren; Jingjie Feng; Ran Li; Yi Duan; Xiaolong Cheng (Ecohydrology & Hydrobiology, 2026)

Combined bearing capacity of spudcan considering installation effect in clay - Ye Tian; Jiang Tao Yi; Si Yu Li; Hong Yu Tang; Xiao Han; Jing Nian Ran (Computers and Geotechnics, 2026)

Regulating radical pathways in highly selective photon–phonon synergistic methane oxidation by tuning Au nanoparticle size over Au–ZrO2 - Shengrong Zhou; Zitong Bao; Yuhang Shao; Xiaolei Guo; Xinru Jiang; Yi Xie; Dong Fang; Ran Ran; Guangzhao Li; Feng Zeng; Hongwei Zhang (Chemical Engineering Journal, 2026)

Active intermediate water-mediated kinetic promotion for synergistic solar evaporation and photocatalytic mineralization - Xuanting Li; Jinchi Li; Xinrong Huang; Qian Chen; Xinyu Li; Hongbing Wang; Jiang Gong; Ran Niu; Yi Lu; Xiaoke Li (Chemical Engineering Journal, 2026)

Hydrodynamic-driven microbial community assembly and coalescence shape nitrogen transformation in river confluence - Cizhang Hui; Hongwu Tang; Qihua Ran; Dongfang Liang; Yi Li; Saiyu Yuan (ENGINEERING Environment, 2026)

A chimeric PRRSV vaccine with dual Nsp2 deletions elicits cross-lineage protection against heterologous challenge - Zhuo-ran Miao; Bo Han; Ling-zhai Meng; Zhen-hui Ren; Yi-han Lu; Jing Li; Wen Sun; Shi-qin Zhang; Jia Wang; Jin-jin Ma; Jia-Lu Li; Yu-tong Zhu; et al. (The Veterinary Journal, 2026)

GIS-based Geotourism Route Design in Changbaishan Global Geopark - Junbo Zhao; Jinxin He; Jian Yi; Xiangjin Ran; Jiaming Li (Geoheritage, 2026)

Structure-driven RNA remodeling underlies broad substrate recognition by NSUN2 - Qian Hu; Wen Yang; Yunyun Yu; Ran Yi; Yutong Zhang; Leyuan Duan; Fudong Li; Kaiming Zhang; Qingguo Gong; Shanshan Li (Science China Life Sciences, 2026)

Deep learning-based downscaling of ocean surface vector wind over the Taiwan Strait and its adjacent seas with Pangu-weather - Jun Yi; Xiang Li; Jiuke Wang; Yunfei Zhang; Ran Yang; Yafei Nie (Journal of Marine Systems, 2026)

Speciation-dependent bioaccessibility of lead in e-waste dismantling soils: Synchrotron spectroscopy reveals molecular controls across physiological compartments - Jian Liu; Yi-Fan Li; Yi-Heng Wang; Dong-Xing Guan; Hao-Ran Guan; Yi-Ren Li; Xing-Mei Liu (Journal of Hazardous Materials, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Integrated metabolomic and transcriptomic analyses unravel the function of quercetin in enhancing grape resistance to anthracnose - Meng-Fei Li; Ming-Yi Wang; Fu-Lai Han; Zhe Zhang; Ya-Lin Liu; Meng-Ran Li; Yu-Fei Li; Jie Yang; Xin Liu; Guang-Chao Liu (Postharvest Biology and Technology, 2026)

Pollution characteristics of Litopenaeus vannamei greenhouse effluents and purification performance of a combined flocculation–ecological floating bed system - Shanyuan Xue; Guo Li; Ensheng Zhu; Weizhen Zhang; Jiao Ran; Zhe Li; Yu Zhao; Jingru Hu; Jing Dong; Yingxue Yi; Dan Zhou; Qiang He; et al. (Journal of Environmental Chemical Engineering, 2026)

Tailoring the microenvironment of ruthenium centers at poly(ionic liquid) frameworks for mild reverse water gas shift reaction - Rui Wang; Yi-Ran Du; Jia-Ni Li; Jing-Wen Sun; Zhao-Rong Yan; Bao-Hua Xu (Chemical Engineering Journal, 2026)

Revegetation mechanisms and influence factor in alpine mining areas: a case study of the Muli mining area, Qinghai-Tibet Plateau - Kaixin Zhang; Qingqiu Hou; Haibo Feng; Linxue Ju; Jianwei Zhou; Jun Li; Ruimin Xiong; Yi Zhu; Xiaoming Zheng; Ran Li; Chunguang Wang (Plant and Soil, 2026)

Targeting ACSL4: A potential strategy to alleviate deoxynivalenol-mediated intestinal ferroptosis, oxidative stress, and immunosuppression in Channa argus - Yi-Ran Zhao; Tong-Hao Wang; Ze-Xin Zhao; Xiao-Tian Niu; Hong-Ming Lv; Yan-Bing Li; Yang Cao; Mu-Yang Li (Aquaculture, 2026)

Intercropping significantly elevates carbon sequestration by mitigating the decline in soil total carbon caused by excessive phosphorus-application - Chuan-Lin Xiao; Ran An; Jiu-Dong Zhang; Yi Xing; Xing-Guo Bao; Rui-Peng Yu; Hans Lambers; Xiang Wang; Long Li (Soil and Tillage Research, 2026)

Emergence of a novel porcine reproductive and respiratory syndrome virus strain inducing biphasic temperature fluctuations in Tianjin, northern China - Jia Wang; Yi-Han Lu; Bo-Han; Hai-Tao Yang; Xin-lei Li; Wen Sun; Shi-Qin Zhang; Zhuo-Ran Miao; Xue-Jiao Cheng; Chun-Xue You; Ying-Feng Sun (Research in Veterinary Science, 2026)

Low doses of chlorothalonil cause testicular impairment in mammals through the antimicrobial-like mechanism - Han-Zhang Wang; Yi-Ming Xiong; Shi-Lin Song; Qian-Cheng Zhao; Xuan-Yue Chen; Jing-Ran Gao; Yuan-Yuan Li; Zhan-Fen Qin (Journal of Hazardous Materials, 2026)

Isolation and identification of spoilage bacteria from kiwifruit and analysis of the antagonistic activity of three Bacillus strains against these bacteria - Ang Liu; Wen-xin Li; Yi Liu; Xing-lin Ran; Bo-yu Dong; Qiu-ping Yao; De-quan Zhu (Food Control, 2026)

Integrative analysis of DEHP exposure and prostate cancer: Mechanistic insights and predictive modeling - Wen-Cai Zheng; Wen-Tao Xu; Chao-Ran Chen; Fei Lin; Shao-Hao Chen; Xiao-Dong Li; Xiong-Lin Sun; Qing-Shui Zheng; Yong Wei; Xue-Yi Xue; Zhi-Bin Ke; Ning Xu (Environmental Pollution, 2026)

Decoupling detoxification from resource recovery: Mechanisms of organic electromigration control in bipolar membrane electrodialysis - Hao-Ran Yang; Zhi-Hua Yuan; Chang-Jiang Li; Yan-Fang Guan; Jiuyang Lin; Mohammad Younas; Xinfei Dong; Yi-Hong Jiang; Yu-Ming Zheng (Chemical Engineering Journal, 2026)

Analysis of the resistance and flow characteristics of a square diffuser under adjacent influence conditions based on design of experiments - Haimeng Li; Wei Xu; Ran Gao; Xinyu Zhang; Chi Zhang; Yan Tian; Yi Wang; Ruoyin Jing (Building and Environment, 2026)

Breaking the antimicrobial resistance dilemma: marine natural products, a treasure trove for the development of new anti-Staphylococcus aureus drugs - Peng-Jie Li; Liu-Xia Lv; Xi-Zhen Cao; Jian-Yu Liu; Ji-Xiu Gao; Hao-Ran Li; Gulab Said; Dan Chen; Bo Yao; Xin Liu; Mei-Yan Wei; Xiao-Ping Yang; et al. (Marine Life Science & Technology, 2026)
Antimicrobial resistance (AMR) affects multiple fields, including medicine, pharmacy, food safety, and animal husbandry, and poses a major threat to public health and economic development. Staphylococcus aureus has emerged as one of the most critical bacterial pathogens due to its widespread prevalence and significant genetic plasticity. This review outlines currently approved small-molecule drugs for clinical use and their mechanisms in controlling bacterial infections and antimicrobial resistance, highlighting the development of novel agents as an effective strategy to combat AMR. Special emphasis is placed on the antibacterial activity of marine-derived natural products (MNPs) against S. aureus , and a systematic analysis is presented for the first time on the structures, origins, activities, and structure–activity relationships of 1,192 compounds reported in 468 publications from 1977 to 2025. Among these, 36 MNPs exhibited significant activity against both methicillin-sensitive S. aureus and methicillin-resistant S. aureus (MIC ≤ 1 µg/mL). Macrolides and peptides represented the most prevalent structural classes, with compounds displaying potent activity accounting for 24% and 27% of the total active compounds, respectively. Further drug-likeness analysis shows that MNPs have promising therapeutic potential. Among the 160 highly active MNPs, over 80% have suitable lipid-water partition coefficients, and 41% fully meet Lipinski's Rule of Five. Structural analysis reveals tetrahydrofuran, tetrahydropyran, and sugar units as the most common motifs, present in 20, 16, and 14 compounds, respectively. Technologies and strategies to accelerate the development of marine-derived antibacterial drugs are also proposed. This will serve stakeholders across diverse sectors by supporting cross-sectoral coordination to address AMR.

A multiscale risk operation and decision making model for inter-basin water diversion project under climate variability - Juan Chen; Zhen-ran Zhang; Yi-fan Liang; Xiao-hui Fan; Jian-qing Xie; Zhen Li; Ping-an Zhong (Environmental Research, 2026)

Alkali promotion in nonmetallic boron-based catalysts: Establishing structure–activity correlations for selective methane oxidation - Ran Yan; Penghui Li; Siyu Liu; Xindi Zhang; Leisu Li; Chenxin Zhang; Shaolong Wan; Jingdong Lin; Xiaodong Yi; Lingtao Liu; Shuai Wang (Chemical Engineering Journal, 2026)

Simultaneous activation of pyroptosis and cGAS-STING pathway with iridium(III) thiophene complexes for enhanced oral squamous cell carcinoma sono-immunotherapy - Jia-Wen Chen; Peng Wang; Jia-Ying Zhou; Yi-Fei Luo; Yi-Ling Li; Jia-Yin Wu; Ling-Ran Li; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2026)

Sex differences in locomotor recovery across mating contexts in Drosophila melanogaster - Rui Han; Jun Zhang; Xin-Hui Chen; Jing-Wen Duo; Yi-Yi Li; Yi-Ran Chen; Si-Tong Chen; Lin-Xiang Liu; Xiang-Haoran Lin (Behavioural Processes, 2026)

Regulate Root Stystem Development by Promoting NO Synthesis Via the NR Pathway after Iron Deficiency in Pears - Wankun Liu; Min Li; Min Liu; Jiankun Song; Chenglin Liang; Yingjie Yang; Dingli Li; Ran Wang; Yi Lv; Jianlong Liu (Journal of Plant Growth Regulation, 2026)

Comprehensive micellar / reversed-phase two-dimensional liquid chromatography for separation and identification of phenolic compounds in herbal tea by multivariate statistical analysis - Qian-Xue Shen; Yi-Wen Wu; Xin-Ran Ma; Jun Cao; Li-Hong Ye (Analytica Chimica Acta, 2026)

Study on the Applicability of Intelligent Recognition Algorithms to Different Types of Subgrade Defects - Yu-xuan Han; Yan-li Qi; Yi Zhang; Yi-guo Xue; Jiang Zhao; Fan-meng Kong; Sheng-yong Dong; Gang Li; Xin-shun Li; Ao-xiong Shu; Hao-ran Zhu (Applied Geophysics, 2026)

Consolidated combined V-H-M-T capacity of a suction caisson in clay - Hao Ran Li; Xiu Zhe Wang; Jiang Tao Yi; Hong Yu Tang; Xiao Han (Ocean Engineering, 2026)

Experimental and numerical investigation on the dynamic response of a 15 MW semisubmersible floating offshore wind turbine including 1-mooring line failure scenario - Ikjae Lee; Da Li; Shenglei Fu; Cong Yi; Moohyun Kim; Alex Ran; Tuanjie Liu (Ocean Engineering, 2026)

Curcumin-mediated photodynamic action disturbs TOM70-depedent MIC60 import to damage mitonchondria against breast cancer - Xiang-Yi Zhao; Min Yan; Liang Zheng; Chang-Long Gou; Qi Huang; Liu-Gen Li; Xin-Ran Yu; Jing-Yu Lu; Cui Hu; Si-Han Zhang; Cunqing Kong; Fan Leng; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

Coupled CFD-DEM modeling of fine particles and fibers migration and clogging mechanisms in bridging regions - Ran Lin; Yinjian Huang; Jinzhou Zhao; Lan Ren; Zhihao Yu; Zhiqiang Li; Jianfa Wu; Yi Song; Cheng Shen (Computers and Geotechnics, 2026)

Close-packed metal organic frameworks enabled high-energy solid-state lithium metal batteries - Yining Zhang; Hongsheng Shi; Yuyao Zhang; Xin Chen; Shuanghong Wang; Jinjiang Liang; Qiong Yuan; Tianyi Gao; Ran Wei; Haochen Zhang; Tao Li; Tianquan Lin; et al. (Chemical Engineering Journal, 2026)

Keystone microbes mediate root traits and phosphorus uptake to enhance maize crop productivity in intercropping systems - Yi-Wen Zhao; Ran An; Jiu-Dong Zhang; Rui-Peng Yu; Yi Xing; Xing-Guo Bao; Jing-Jing Peng; Long Li (Plant and Soil, 2026)

Regulatory mechanisms of total phosphorus on N2O concentrations: A case study of Dongting lake - Jie Liang; Yi Li; Weixiang Li; Ziqian Zhu; Xiang Gao; Ran Du; Lan Lu; Jing He; Chaozhong Tan; Rong Wu; Jikai Liao (Water Research, 2025)

Microbial metabolic functions, rather than taxonomic composition, predominantly shape the distribution of antibiotic resistance genes in an effluent-impacted hyporheic zone - Yina Zou; Wenlong Chen; Longfei Wang; Yi Li; Ziyi Wang; Ran Tao (Water Research, 2025)

Role of LuxS/AI-2 quorum sensing in Staphylococcus aureus biofilm formation, intestinal damage and pathogenesis in loach (Misgurnus anguillicaudatus) - Miaomiao Chen; Yuyang Duan; Wenqing Yang; Jiajia Chen; Qiujin Wang; Yuyan Xu; Xuetian Li; Xinyu Ran; Yi Li (Fish & Shellfish Immunology, 2025)

Floc-granule microbial symbiosis drives DNRA in anammox bacteria via cross-feeding for complete autotrophic nitrogen removal - Yulong Yang; Wen-Bo Nie; Xin Tan; Lili Li; Chenhui Yu; Shibo Fu; Ke-Di Peng; Yi Luo; Xiao Ran; Zhihong Zheng; Jin Xu; Jun Li; et al. (Chemical Engineering Journal, 2025)

Targeted-nanoformulation of cannabidiol attenuates endothelial injury and platelet hyperactivation for combating silicosis - Sirong Chang; Yue Sun; Wenyue Zhang; Yi Guo; Huning Zhang; Nan Li; Ran An; Mengsi Xiao; Siwei Zou; Na Zhang; Kai Wang; Anning Yang; et al. (Chemical Engineering Journal, 2025)

A self-activated CO-releasing microneedle patch for treating diabetic foot ulcer biofilm infection - Linpei Li; Menghao Wei; Haixia Zhang; Zilong Zhang; Xiaojuan Zhao; Zhichao Ran; Yi Li; Yanwei Yang; Ningning Song; Chaoqun Liu (Chemical Engineering Journal, 2025)

Genome-Wide Identification and Expression Profiling of Oryza Sativa Sulfotransferase Genes Associated with Oxyfluorfen and Fluroxypyr-Meptyl Metabolism - Li Qing Zeng; Xiao Yu Zhong; Nian Hua Teng; Xu Zhen Shi; Yi Zhuo Wang; Xi Ran Cheng; Ying Yu Zeng; Zhao Jie Chen (Tropical Plant Biology, 2025)

Identification, Characterization, and Expression Profiling of Oryza Sativa Betaine Aldehyde Dehydrogenase Genes Exposed to Realistic Environmental Contamination of Oxyfluorfen - Yi Zhuo Wang; Jun Jin Lu; Xu Zhen Shi; Ya Nan Qu; Li Qing Zeng; Xiao Liang Liu; Xi Ran Cheng; Yan Hui Wang; Zhao Jie Chen (Tropical Plant Biology, 2025)

Quantitative Evaluation of Incomplete Stent Apposition in Intracranial Aneurysms Using Optical Coherence Tomography: a Porcine Model Study - Zhuangzhuang Wei; Ji Ma; Zhike Zhang; Shuailong Shi; Shuhai Long; Shaofeng Shui; Lei Yan; Yan Song; Yi Tang; Ye Wang; Jie Yang; Yuncai Ran; et al. (Translational Stroke Research, 2025)

The NLRP3 inflammasome: a pivotal orchestrator of multisystem diseases—from molecular mechanisms to therapeutic innovation - Shu-yan Xiao; Ya-hui Lv; Yin-min Ji; Yi Dong; Mei-cen Liu; Tao Li; Xiao-ran Cui; Yi Hu (Molecular Biology Reports, 2025)

The critical role of mitophagy in cell senescence-mediated pulmonary fibrosis and potential therapeutic strategies - Xing-Yi Chen; Dong-Mei Wang; Ya Zhou; Li Liu; Tao Zhu; Zhao Ran; Mei-Hong Lu; Ben-Rong Mu (Molecular Biology Reports, 2025)

Development of novel melatonin-isatin hybrids as multifunctional agents for Alzheimer’s disease - Ying-Ying Zhong; Jun‑Ze Deng; Qin Wang; Li Chen; Zi-Hang Yang; Ya-Mei Zhang; Lu‑Yi Zhou; Yi-Ran Li; Jia-Qiang Wu; Xiao-Qin Wang (Molecular Diversity, 2025)

Identification, characterization, and expression profiling of putrescine synthesis genes associated with bentazone metabolism in Oryza sativa - Li Qing Zeng; Nian Hua Teng; Ying Yu Zeng; Zhi Jiang He; Yi Zhuo Wang; Zhi Zhong Zhou; Xiao Liang Liu; Xi Ran Cheng; Zhao Jie Chen (Genetic Resources and Crop Evolution, 2025)

Identification, characterization, and expression profiling of rice MADS-box transcription factor genes associated with fluroxypyr-meptyl and oxyfluorfen metabolism - Zhi Zhong Zhou; Nian Hua Teng; Jia Lin Liang; Ying Yu Zeng; Yi Zhuo Wang; Li Qing Zeng; Xiao Liang Liu; Xi Ran Cheng; Zhao Jie Chen (Genetica, 2025)

Dual-mode fluorescence/colorimetric aptasensor based on Zn,Ce-MOF nanocomposite for sensitive detection of isocarbophos - Yimeng Li; Jiayao Wang; Yi Ran; Yiwei Liu; Xiaopeng Hu (Analytica Chimica Acta, 2025)

Recovery of siliceous ecosystems promoted Early Silurian climatic cooling - Huan Xu; Bo Ran; Terry T. Isson; Xinyang Chen; Chao Luo; Yi Li; Yiqing Zhu; Tong Sun; Yuyue Han (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Post-heat treatment and pectin addition affect protein digestion and absorption release kinetics in pigs through microstructural and rheological modifications - Xiyu Qin; Xiuying Wu; Caiziyu Yu; Yi Chai; Xiaoxue Liu; Xiaoxu Zhang; Huifang Cai; Mengxuan Lai; Lili Qiu; Yanling Hao; Ran Wang; Yixuan Li; et al. (Food Chemistry, 2025)

Heat treatment affects gastric digestion kinetics but not amino acid bioavailability of milk proteins: a pig study - Xiyu Qin; Caiziyu Yu; Xiaolu Geng; Yi Chai; Xiaoxue Liu; Xiaoxu Zhang; Menghui Wang; Xiaomin Ren; Yanling Hao; Ran Wang; Yixuan Li; Pengjie Wang; et al. (Food Chemistry, 2025)

Ni/Zr co-doping strategy to promote cyclic performance of CaO-based materials for thermochemical energy storage: Experimental and first-principles insights - Zhu-yu Li; Le-ran Li; Jing-yi Liu; Qi Niu; Zhi-mo Fang; Ji-hong Li; Kai Li; Qiang Lu (Chemical Engineering Journal, 2025)

Ceritinib (LDK378) inhibits laryngeal squamous cell carcinoma progression via regulating ROS-induced mitochondrial apoptosis and inducing oxidative stress - Yue Wang; Xiaoli Ren; Pengyan Liu; Ran An; Wenjing Li; Licheng Xu; Yaoyao Dong; Xiaolin Xu; Yi wang; Lei Zhang; Linli Tian (Toxicology and Applied Pharmacology, 2025)

Superhydrophilic hydrolyzed-TEOS modified rPET/PEG/SiO2 membranes for oil-in-water emulsion separation - Panchan Dansawad; Yi Fang; Lixia Cao; Haigang Gao; Cong Xue; Ruifeng Ran; Haofei Nie; Yanxiang Li; Wangliang Li (Journal of Environmental Chemical Engineering, 2025)

A ratiometric fluorescent probe for sensitive detection of benzoyl peroxide and hypochlorite in food - Shun-Qiang Cui; Xin-Yi Liang; Zhi-Qiang Cai; Hou-Qun Yuan; Qiu-Yu Zhang; Yi-Fan Xia; A.K.I.M.A.N.A. Sandra; Ling-Yi Guo; Ran Wang; Shi-Yu Zhao; Yan-Xia Li; Guang-Ming Bao (Food Chemistry, 2025)

Chloride ion-driven activation of Ru-CeO2 for efficient methoxycarbonylation of long-chain alkenes - Yi-Ran Du; Yi-Yu Tao; Jing-Wen Sun; Han-Sheng Li; Rui Zhang; Bao-Hua Xu (Chemical Engineering Journal, 2025)

Biomass-derived organic aerogels endowed flexible polyurethane foam with excellent flame retardance, smoke suppression, bacteriostasis and enhanced mechanical property - Ying-Ming Li; Yao Deng; Hang-Ping Fang; Yi-Ran Li; De-Yi Wang (Chemical Engineering Journal, 2025)

Study on the resistance calculation method for ventilation duct systems under non-fully developed flow conditions - Yi Wang; Sen Yang; Ran Gao; Yan Tian; Ruoyin Jing; Angui Li (Building and Environment, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

A study on the impact of digitalization on green agricultural development and its spatial effects in China - Xiaowen Dai; Yao Li; Ying Qi; Yi Chen; Yanqiu He; Ruiping Ran; Qi Yin (Environment, Development and Sustainability, 2025)

CCP domain containing protein from complement factor H of Paralichthys olivaceus has potential effects against Edwardsiella piscicida infection - Xuan-yue Wang; Yu-ting Du; Xin-yi Jiang; Zhuo-ran Ma; Chao-ran Zhang; Xue-peng Li; Zeng-zhi Yuan; Mo-fei Li (Aquaculture, 2025)

A selenium nanozyme: Light/mercury dual-enhanced oxidase mimicry for simultaneous ultra-sensitive detection and efficient removal of mercury ions, and superior photocatalytic bacterial disinfection - Yu Shi; Dong-hui Li; Chi Zhang; Zheng-ren Wang; Yi-ran Wang; Ru-kang Chen; Yen-ho Chu; Yu-gang Shi; Rammile Ettelaie; Qing Gu (Water Research, 2025)

A novel dynamic membrane-equipped element sulfur-based denitrification reactor for efficient and easily maintainable treatment of high-nitrate wastewater - Na Zhang; Xiang-Li Zeng; Wen-Wei Liao; Meng-Yi Chen; Guijiao Zhang; Da-Heng Ren; Xu-Chen Ba; Min-Kun Zhang; Hao-Ran Xu; Aijie Wang; Hao-Yi Cheng (Water Research, 2025)

Coping or adapting? Exploring regional priority of capacity building for disaster resilience - Yanan Chen; Ran Yi; Jiahe Li; An Chen (Journal of Cleaner Production, 2025)

Study on the influence mechanism of endogenous protein components on the characteristics of distiller's grains starch - Min Huang; Li Li; Xinran Cheng; Ran Qiu; Yi Wang; Xianjiang Zhou; Xuyan Zong (Food Chemistry, 2025)

Logic-gate nanocompiler for oxidative/reductive molecular parallel detection during hepatic ischemia-reperfusion injury - Tao Tang; Fushou Liu; Longshua Qin; Hao Li; Wen-Ping Lin; Yi-Ping Gu; Fangtao Tan; Linfeng Wang; Huan Liu; Mingxi Zhang; Ran Cui (Chemical Engineering Journal, 2025)

A two-level turbulent density-based topology optimization method: A low-resistance U-bend channel flow - Yan Tian; Ran Gao; Yi Wang; Angui Li; Xin Dong; Tong Li; Shengrui Yu (Building and Environment, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

An air balancing method for ventilation systems considering random fluctuations: Flow prediction and operating condition optimization - Yi Wang; Ran Gao; Yan Tian; Ruoyin Jing; Mengchao Liu; Angui Li (Building and Environment, 2025)

Effectiveness of bioretention system with saturated zone and different dry–wet alterations on nitrogen removal: performance and microbial community - Ran Li; Binyu Lu; Wen-wen Liu; Zebing Li; Yi-Ming Kuo (Environmental Geochemistry and Health, 2025)

Phage Therapy Enhances Survival, Immune Response, and Metabolic Resilience in Pacific White Shrimp (Litopenaeus vannamei) Challenged with Vibrio parahaemolyticus - Chao Zeng; Long Qi; Chao-Li Guan; Yu-Lin Chang; Yu-Yun He; Hong-Zheng Zhao; Chang Wang; Yi-Ran Zhao; Yi-Chen Dong; Guo-Fang Zhong (Fishes, 2025)
Acute hepatopancreatic necrosis disease (AHPND), caused by the bacterium Vibrio parahaemolyticus, is a major threat to global shrimp aquaculture. In this study, we evaluated the therapeutic effects of phage therapy in Litopenaeus vannamei challenged with AHPND-causing Vibrio parahaemolyticus. Phage application at various concentrations significantly improved shrimp survival, with the 1 ppm group demonstrating the highest survival rate. Enzymatic assays revealed that phage-treated shrimp exhibited enhanced immune enzyme activities, including acid phosphatase (ACP), alkaline phosphatase (AKP), and lysozyme (LZM). In addition, antioxidant defenses such as superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-PX), and total antioxidant capacity (T-AOC) significantly improved, accompanied by reduced malondialdehyde (MDA) levels. Serum biochemical analyses demonstrated marked improvements in lipid metabolism, particularly reductions in triglyceride (TG), total cholesterol (TC), and low-density lipoprotein (LDL), alongside higher levels of beneficial high-density lipoprotein (HDL). Transcriptomic analysis identified 2274 differentially expressed genes (DEGs), notably enriched in pathways involving fatty acid metabolism, peroxisome functions, lysosomes, and Toll-like receptor (TLR) signaling. Specifically, phage treatment upregulated immune and metabolic regulatory genes, including Toll-like receptor 4 (TLR4), myeloid differentiation primary response protein 88 (MYD88), interleukin-1β (IL-1β), nuclear factor erythroid 2-related factor 2 (Nrf2), and peroxisome proliferator-activated receptor (PPAR), indicating activation of innate immunity and antioxidant defense pathways. These findings suggest that phage therapy induces protective immunometabolic adaptations beyond its direct antibacterial effects, thereby providing an ecologically sustainable alternative to antibiotics for managing bacterial diseases in shrimp aquaculture.

Synergistic coupling of bipolar membrane electrodialysis and Fenton process for sustainable management of landfill leachate reverse osmosis concentrate - Hao-Ran Yang; Changjiang Li; Chiqian Zhang; Xiaohong Lan; Xinfei Dong; Yi-Hong Jiang; Yu-Ming Zheng; Zhi-Hua Yuan (Chemical Engineering Journal, 2025)

Tracking phycocyanin dynamics in East Lake using Landsat-8 and generalized additive models: impact of COVID-19 and conservation efforts - Jincan Tang; Wen-Wen Liu; Ran Li; Enmin Zhao; Yi-Ming Kuo (Environmental Monitoring and Assessment, 2025)

Phenol-driven ammonium recovery from coal chemical wastewater in a bioelectrochemical system (BES) - Ran Zeng; Li-Hui Yang; Si-Yuan Zhai; Cheng-Yan Liu; Na Lin; Qing-Hua Ou-Yang; Yan-Hua Xu; Ai-Jie Wang; Hao-Yi Cheng (Journal of Hazardous Materials, 2025)

An emulsion gel made by waxy maize starch hydrogel incorporated with tea polyphenols/exopolysaccharides: Structure and stability properties, antioxidant and delivery function - Cuicui Duan; Shunan Hu; Ran Wang; Cheng Wu; Yi Zhang; Lin Ma; Fumin Ma; Xiaolei Li; Dan Li (Food Bioscience, 2025)

Schistosoma japonicum cystatin attenuated CLP-induced sepsis in mice though inducing tolerogenic dendritic cells and regulatory T cells - Yi-Xiang Wang; Yi-Dan Ma; Hui-Hui Li; Wen-Juan Duo; Qi-Wang Jin; Kai-Jun Zhou; Yan-Ran Gao; Jun-Nan He; Yu-Jie Xie; Liang Chu; Xiao-Di Yang (Comparative Immunology, Microbiology and Infectious Diseases, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Evaluation of Geosites in Changbaishan Global Geopark based on Fuzzy AHP and TOPSIS - Jiaming Li; Jinxin He; Peng Lu; Xiangjin Ran; Jian Yi (Geoheritage, 2025)

Anthracnose caused by Colletotrichum siamense on rambutan in China - Gengxin Chen; Jinhua Sun; Jiaming Cui; Yu Wang; Yajun Ran; Deqiang Gong; Yi Yang; Meijiao Hu; Min Li (Crop Protection, 2025)

The simulated in vitro infant gastrointestinal digestion of lipid droplets covered with milk fat globule membrane components: The role of interface layers - Zhixi Li; Yu Cao; Xiankang Fan; Hui Zhou; Pengjie Wang; Hao Zhang; Yi Wang; Ran Wang; Jie Luo (Food Research International, 2025)

The mechanisms of salt weathering responsible for sandstone deterioration in the Yungang Grottoes, China - Xi Yang; Xiao-Wei Jiang; Kai-Gao Ouyang; Tao-Tao Ji; Yi-Fan Gao; Xiao-Hong Geng; Ran Niu; Ji-Zhong Huang; Hong-Bing Yan; Li Wan (Engineering Geology, 2025)

Sonneralignan A, a new lignan from the fruit of mangrove Sonneratia apetala - Yue-Yao Li; Jia-Lang Xia; Meng Bai; Kai Liu; Jin-Hua Wei; Zu-Ran Lv; Yong-Hong Liu; Cheng-Hai Gao; Xiang-Xi Yi (Natural Product Research, 2025)

Nitrate ameliorates myelin loss and cognitive impairment in Alzheimer’s disease through upregulation of neuronal sialin and subsequent inhibition of TPPP phosphorylation - Xinyue Chen; Geng Hu; Lirong Chang; Xiaoyu Li; Yi Tang; Yan Wu; Ran Zhang; Chunmei Zhang; Jinsong Wang; Xue Wang; Songlin Wang (Science Bulletin, 2025)

Experimental and numerical study on the hydrodynamic characteristics of a cube fish cage integrated into a wind turbine jacket foundation - Yuan-Mao Zhang; Fen-Fang Zhao; Liu-Yi Huang; Huan-Ran Li; Chun-Wei Bi (Ocean Engineering, 2025)

A comprehensive omics resource and genetic tools for functional genomics research and genetic improvement of sorghum - Chengxuan Chen; Fengyong Ge; Huilong Du; Yuanchang Sun; Yi Sui; Sanyuan Tang; Zhengwei Shen; Xuefeng Li; Huili Zhang; Cuo Mei; Peng Xie; Chao Li; et al. (Molecular Plant, 2025)

A genomic variation map provides insights into potato evolution and key agronomic traits - Qun Lian; Yingying Zhang; Jinzhe Zhang; Zhen Peng; Weilun Wang; Miru Du; Hongbo Li; Xinyan Zhang; Lin Cheng; Ran Du; Zijian Zhou; Zhenqiang Yang; et al. (Molecular Plant, 2025)

Targeting ferroptosis for the treatment of female reproductive system disorders - Rui Ye; Yi-ming Mao; Yi-ran Fei; Yue Shang; Ting zhang; Zhe-zhong Zhang; Yong-lin Liu; Jun-yu Li; Shi-liang Chen; Yi-bo He (Journal of Molecular Medicine, 2025)

Application of extreme gradient boosting for predicting standard penetration test N-values from cone penetration test data - Xiao Han; Jiangtao Yi; Xiaobin Li; Siyu Li; Hongyu Tang; Zhen Wang; Jingnian Ran (Bulletin of Engineering Geology and the Environment, 2025)

Paleoceanographic and paleoenvironmental changes in the high-latitude Southern Ocean during late Quaternary: progress and prospects based on the Chinese Antarctic Expeditions - Li Wu; Rujian Wang; Wenshen Xiao; Qingmiao Li; Kaitao Ni; Ran Xu; Yi Chen (Acta Oceanologica Sinica, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Triptolide exposure triggers ovarian inflammation by activating cGAS-STING pathway and decrease oocyte quality in mouse - Si-Yao Cheng; Yi-Fan Yang; Ya-Long Wang; Zhao-Ping Yue; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2025)

Role of hepatocyte-specific FOXO1 in hepatic glucolipid metabolic disorders induced by perfluorooctane sulfonate - Jing Yang; Longfei Li; Ziwen An; Yi Lv; Ran Li; Jing Li; Mingmei Guo; Heming Sun; Huiling Yang; Lei Wang; Yi Liu; Huicai Guo (Environmental Pollution, 2025)

A method for demand controlled ventilation based on a pressure loss model under conditions of non-fully developed flow - Yi Wang; Ran Gao; Mengchao Liu; Angui Li; Yan Tian; Ruoyin Jing (Building and Environment, 2025)

Topology optimization of bend for reducing the local resistance in a piping and duct system - Yan Tian; Ran Gao; Ruoyin Jing; Yi Wang; Angui Li; Xin Dong; Xinpeng Hao; Zheng Ji (Building and Environment, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

On the permeability-surface area-porosity relationship for dissolving porous media - Kai Li; Ran Hu; Ya-Nan Zhang; Zhibing Yang; Yi-Feng Chen (Advances in Water Resources, 2025)

Research on the source of cinnabar excavated from Sanxingdui site in China based on sulphur and mercury isotope analyses - Qinxin Jiang; Guangyi Sun; Honglin Ran; Yu Lei; Chong Wang; Zhenbin Xie; Fei Tang; Jian Yu; Bisu Zhou; Min Shi; Wan Peng; Chenghui Li; et al. (Archaeological and Anthropological Sciences, 2025)

Urea interfacial polymerization-based ultra-permeable polyamide composite membrane for efficient piggery wastewater purification - Lingfang Huang; Xiaocai Cui; Huimin Dang; Yi Huang; Qian Li; Ting Ran; Xingtao Zuo; Jiajie He; Yun Zhou (Chemical Engineering Journal, 2025)

Full-spectral response of mesoporous Z-scheme nanoheterojunction NaYF4:Yb,Tm@ZnO/BiOI photocatalysts for simultaneous contaminant and pathogen elimination in wastewater - Wenqi Liu; Changyuan Zhang; Ran Yi; Mengyu Di; Dan Shan; Yang Wu; Xiaoyu Linghu; Chang Li; Baiqi Wang (Process Safety and Environmental Protection, 2024)

Gelatin/polyvinyl alcohol films loaded with doubly stabilized clove essential oil chitosomes: Preparation, characterization, and application in packing marinated steaks - Cenchen Ran; Qingqing Li; Mou Zhao; Haotian Cui; Yi Yang; Kui Diao; Yazhi Liu; Shiling Lu; Juan Dong; Qingling Wang (Food Chemistry, 2024)

Sensitive detection of Hg(II) on MoS2/NiS2 based on interfacial engineering to accelerate the Ni2+/Ni3+ cycle: Identification the role of atomic-level heterojunction-induced electron transfer in electroanalysis - Huan Xu; Hao-Ran Li; Jing-Yi Li; Jian-Jun Qu; Shan-Shan Li (Analytica Chimica Acta, 2024)

Boosting bioelectricity generation in bioelectrochemical systems with nitrogen-doped three-dimensional graphene aerogel anode - Yi-Xuan Wang; Xiao-Li Liu; Wen-Qiang Li; Yi-Ran Wang; Ke-Wan Li; Zhi-Cheng Pan; Yang Mu (Water Research, 2024)

LiF-enriched interphase promotes Li+ desolvation and transportation enabling high-performance carbon anode under wide-range temperature - Wenbin Luo; Kuo Li; Tu Ran; Di Ma; Xingkun Chen; Haisong Wang; Yi Cheng; Xiaofei Yang (Chemical Engineering Journal, 2024)

Polyamide and deep eutectic solvent assisted matrix solid-phase dispersion microextraction for strong hydrophobic compounds - Yi-Wen Wu; Xin-Ran Ma; Xin Peng; Xudong Cai; Jun Cao; Li-Hong Ye (Sustainable Chemistry and Pharmacy, 2024)

Gigantic gastropods from the Middle Triassic Qingyan biota of Guizhou - Xin Sun; Li Tian; Chuan-Yuan Liu; Xiao He; Dao-Liang Chu; Xue Miao; Shi-Yan Zhang; Yi-Ran Cao; Pei-Shan Li; Jin-Nan Tong; Hai-Jun Song (Palaeoworld, 2024)

Freshwater microconchids from the Tanzhuang Formation (Middle-Late Triassic) in North China - Hao Yang; Yue Su; Hui-Jun Chen; Yi-Ran Cao; Meng-Yang Zhang; Rui Li; Dao-Liang Chu (Palaeoworld, 2024)

Loss of CHCHD2 Stability Coordinates with C1QBP/CHCHD2/CHCHD10 Complex Impairment to Mediate PD-Linked Mitochondrial Dysfunction - Yan-Lin Ren; Zheng Jiang; Jia-Yi Wang; Qin He; Si-Xu Li; Xiao-Jing Gu; Yang-Ran Qi; Min Zhang; Wen-Jie Yang; Bei Cao; Jing-Yu Li; Yi Wang; et al. (Molecular Neurobiology, 2024)

B/N modified carbon nanofiber mesh covered with layered double hydroxide for large current overall water splitting - Ji Qi; Chunqi Zhu; Jianing Hu; Shuai Ran; Tauqeer Ahmad; Siraj Ullah; Lixu Chen; Yi Chen; Yuqing Xia; Xue Sun; Chuang Li; Xiao Chen; et al. (Fuel, 2024)

Salinity responsive mechanisms of sulfur-based mixotrophic denitrification and ectoine induced tolerance enhancement - Ran Li; Ya-Nan Hou; Haibo Li; Yi Han; Daohong Zhang; Yuanyuan Song; Cong Huang; Jianbo Guo; Zhihua Liu; Wei Wei; Bing-Jie Ni (Chemical Engineering Journal, 2024)

Taming the anchor and conversion of polyselenides with a self-reinforcing host in lithium–selenium batteries - Hongyan Li; Wenda Dong; Yueqiang Cao; Tarek Barakat; Marvin Laboureur; Mao-Jin Ran; Zhi-Yi Hu; Hongxian Zhang; Cheng-Bin Jin; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2024)

Water flush boosts performance of elemental sulfur-based denitrification packed-bed systems: Optimization and mechanisms - Jia-Min Xu; Heng Dong; Hao-Ran Xu; Yi-Lu Sun; Yang Yu; Li-Ying Zhang; Gen-Ping Yi; Wen-Ke He; Chang-Min Wu; Ai-Jie Wang; Hao-Yi Cheng (Bioresource Technology, 2024)

Behavior of calcium lignosulfonate under oxygen pressure acid leaching condition - Sijie Yang; Yuhu Li; Yudong Yang; Ran Liu; Yi Zhao (Hydrometallurgy, 2024)

Porous carbon prepared by thermal dissolution of coal and biomass for high-performance supercapacitors - Yi Liu; Wei-Dong Cao; Xing Fan; Ran-Ran Hou; Xiang Bai; Xiao-Yun Zhang; Yan Li; Guo-Ming Zhao; Peng Liang (Fuel, 2024)

Immobilization of Nickel- and Cobalt-Based Complexes in NH2-UiO-66 for Efficient CO2 Photoreduction - Yu Jiang; Si-Chao Liu; Li-Ping Zhang; Guo-Wei Guan; Yi-Tao Li; Shuang Ni; Run-Yuan Jiang; Su-Tao Zheng; Hao-Ran Liu; Hao-Ling Lan; Qing-Yuan Yang (Chemical Engineering Journal, 2024)

The protective effect and mechanism of piperazine ferulate in rats with 5/6 nephrectomy-caused chronic kidney disease - Xiu-Meng Zhang; Xin-Ran Min; Dan Li; Bo Li; Yi-Xin rui; Hong-Xiao Xie; Rong Liu; Nan Zeng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

The fabrication of Mn single atoms/clusters on Al2O3 for enhanced catalytic NO oxidation - Xiao-Ke Hou; Hui-Xin Zhang; Yi-Bo Wang; Jin-Ping Zhang; Xin Gao; Lei Chen; Chao Li; Hong-Mei Jing; Chi He; Qiang Lu; Chun-Ran Chang (Fuel, 2024)

Effect of recycled polypropylene on migration of six processing aids in polypropylene film to milk - Yi-Qi Liu; Ze-Kun Li; Hao-Ran Zhang; Zhi-Wei Wang; Chang-Ying Hu (Food Packaging and Shelf Life, 2024)

Promoting effect of polyoxometallic acid modification on the NH3-SCR performance of Mn-based catalysts - Yi Dong; Mingchu Ran; Xiao Zhang; Saisai Lin; Weixian Li; Yang Yang; Hao Song; Weihong Wu; Shaojun Liu; Chenghang Zheng; Xiang Gao (Journal of Environmental Chemical Engineering, 2024)

Associations between exposure to phthalates and liver function among women undergoing assisted reproductive technology - Yi Wang; Li Yin; Yao-Yao Du; Hong-Mei Liao; Juan Li; Wen Yao; Xiao-Qiong Yuan; Qing-Chun Guo; Tao-Ran Deng; Na Guo; Min Zhang; Qiang Zeng; et al. (Environmental Toxicology and Pharmacology, 2024)

Treatment of chromium-containing sludge using sintering and ironmaking combined technology: A risk-reducing strategy for environmental impact - Shengxuan Fan; Jinchao Wei; Xiaorong Xu; Ran Yan; Qian Li; Ying Liu; Yanjun Huang; Yi Wang; Guozhi Fan; Lei Zhang (Journal of Environmental Management, 2024)

2D ZIF-8 derived N-doped porous carbon nanosheets for high-performance Li-Se batteries - Xu-Wei Luo; Ming-Ran Zhou; Mao-Jin Ran; Dao-Xiang Xun; Jia-Le He; Zhi-Yi Hu; Hemdan S.H. Mohamed; Jing Liu; Li-Hua Chen; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2024)

Genome constitution and evolution of Elymus atratus (Poaceae: Triticeae) inferred from cytogenetic and phylogenetic analysis - Lu Tan; Dan-Dan Wu; Chang-Bing Zhang; Yi-Ran Cheng; Li-Na Sha; Xing Fan; Hou-Yang Kang; Yi Wang; Hai-Qin Zhang; Marcial Escudero; Yong-Hong Zhou (Genes & Genomics, 2024)

Short-term effects of exposure to cold spells on blood pressure among adults in Nanjing, China - Tian-Lin Li; Bei-Jing Cheng; Nan Jiang; Xing-Chen Meng; Chun Wang; Yang Huang; Ke Meng; Hui Li; Xin-Yi Zhu; Ran Liu (Air Quality, Atmosphere & Health, 2024)

Variations in the concentration, inventory, source, and ecological risk of polycyclic aromatic hydrocarbons in sediments of the Lake Chaohu - Hao-Ran Tian; Xi-Tao Zhang; Li-Li Zhao; Shu-Chuan Peng; Ji-Zhong Wang; Yi-Han Chen (Marine Pollution Bulletin, 2024)

Experimental optimization and mechanism analysis of extracting flavonoids with the supramolecular solvents-based methods - Zhi-lu Yu; Shi-yi Hou; Li-mei Lin; Yu-ran Chu; Ya-mei Li; Zhi-min Zhang; Jing Yan; Bo-hou Xia (Sustainable Chemistry and Pharmacy, 2024)

Curvularin derivatives from the marine mangrove derived fungus Penicillium sumatrense MA-325 - Yi-Ran Wang; Yu-Liang Dong; Xiao-Ming Li; Xiao-Shan Shi; Hong-Lei Li; Ling-Hong Meng; Rui Xu; Bin-Gui Wang (Phytochemistry, 2024)

Promoting nitrogen conversion in aerobic biotransformation of swine slurry with the co-application of manganese sulfate and biochar - Xuan Wu; Xinyu Zhao; Guorong Yi; Wanqiang Zhang; Runyu Gao; Daniel Kuok Ho Tang; Ran Xiao; Zengqiang Zhang; Yiqing Yao; Ronghua Li (Journal of Environmental Management, 2024)

Phthalate drives splenic inflammatory response via activating HSP60/TLR4/NLRP3 signaling axis-dependent pyroptosis - Xin-Ran Ge; Yi Zhao; Hao-Ran Ren; Fu-Wei Jiang; Shuo Liu; Ming Lou; Yi-Feng Huang; Ming-Shan Chen; Jia-Xin Wang; Jin-Long Li (Environmental Pollution, 2024)

The occurrence and distribution characteristics of microbial necromass carbon in lake sediments - Yi Liu; Xiaodong Nie; Fengwei Ran; Shilan Wang; Shanshan Liao; Aoqi Zeng; Zhongwu Li (CATENA, 2024)

Intercropping efficiently utilizes phosphorus resource in soil via different strategies mediated by crop traits and species combination - Ran An; Rui-Peng Yu; Yi Xing; Jiu-Dong Zhang; Xing-Guo Bao; Hans Lambers; Long Li (Plant and Soil, 2024)

Tricarboxylic acid cycle metabolites: new players in macrophage - Ying Yang; Bing-Bing Cui; Jian Li; Jiao-Jiao Shan; Jun Xu; Cheng-Yong Zhang; Xiao-Tong Wei; Ri-Ran Zhu; Jing-Yi Wang (Inflammation Research, 2024)

Distribution and transformation characteristics of water vapor field in the fissured rock mass and its ecological significance - Danhui Su; Jianwei Zhou; Haibo Feng; Ran Li; Xiaoming Zheng; Yi Zhu; Xu Han; Qingqiu Hou (Journal of Hydrology, 2024)

Multifunctional Eu3+-MOF for simultaneous quantification of malachite green and leuco-malachite green and efficient adsorption of malachite green - Yi-Fan Xia; Hou-Qun Yuan; Chen Qiao; Wei Li; Ran Wang; Peiyao Chen; Yan-Xia Li; Guang-Ming Bao (Journal of Hazardous Materials, 2024)

Microbiome resistance mediates stimulation of reduced graphene oxide to simultaneous abatement of 2,2′,4,4′,5-pentabromodiphenyl ether and 3,4-dichloroaniline in paddy soils - Yi Sun; Ying Teng; Ran Li; Xia Wang; Ling Zhao (Journal of Hazardous Materials, 2024)

Phase diagram and permeability evolution for dissolving vertical fractures in a gravity field - Kai Li; Ran Hu; Xu-Sheng Chen; Zhibing Yang; Yi-Feng Chen (Advances in Water Resources, 2024)

Phosphorus species transformation and recovery in deep eutectic solvent-assisted hydrothermal carbonization of sewage sludge - Rui Dou; Fan Gao; Yi Tan; Huan-Ran Xiong; Zhi-Xiang Xu; Sameh M. Osman; Li-Jun Zheng; Rafael Luque (Sustainable Chemistry and Pharmacy, 2024)

LSTM time series NDVI prediction method incorporating climate elements: A case study of Yellow River Basin, China - Yan Guo; Lifeng Zhang; Yi He; Shengpeng Cao; Hongzhe Li; Ling Ran; Yujie Ding; Mikalai Filonchyk (Journal of Hydrology, 2024)

Hydrochar-based facile and greenwood bio-adhesives production from distilled spent grain - Zhi-Xiang Xu; Huan-Ran Xiong; Rui Dou; Yi Tan; Yong-Xing Chen; Li-Jian Leng (Chemical Engineering Journal, 2024)

Retention Efficiencies of Vegetative Filter Strips in Reducing Agricultural Nonpoint Source Pollution in Jianghan Plain: Experiments and VFSMOD Modeling - Ran Li; Wen-wen Liu; Enmin Zhao; Yi-Ming Kuo (Water, Air, & Soil Pollution, 2024)

ATG5 Knockdown Attenuates Ischemia‒Reperfusion Injury by Reducing Excessive Autophagy-Induced Ferroptosis - Hua Zhu; Yi Zhong; Ran Chen; Lei Wang; Yuntao Li; Zhihong Jian; Lijuan Gu; Xiaoxing Xiong (Translational Stroke Research, 2024)

Dual-emissive Eu(III)-functionalized metal-organic frameworks for visual, rapid, and intelligent sensing of albendazole and albendazole sulfoxide in animal-origin food - Hou-Qun Yuan; Yi-Fan Xia; Yu-Fei Zhong; Wei Li; Hongda Zhu; Ran Wang; Peiyao Chen; Zhiming Gao; Xiangwei Zhu; Yan-Xia Li; Guang-Ming Bao (Analytica Chimica Acta, 2024)

Grain-size, coarse fraction lithology and clay mineral compositions of surface sediments from Ross Sea, Antarctica: implications for their provenance and delivery mode - Li Wu; Longwei Li; Rujian Wang; Hebin Shao; Yi Chen; Zipei Lin; Yue Liu; Wenshen Xiao; Ran Xu (Frontiers in Marine Science, 2024)
Knowledge on spatial distribution, provenance and delivery mode of surface sediment aids in interpretation of nearby sediment records for paleoenvironmental reconstruction. Such knowledge, however, remains largely unknown for the modern Ross Sea, Antarctica: a key region for understanding the dynamical behavior of Antarctic Ice Sheet over geological past. In this study, we address this gap by analyzing the grain-size distribution, coarse fraction (>250 μm) lithology, and clay mineralogy of a set of surface sediment samples covering the whole Ross Sea continental shelf. Our data reveals that the sediments were mostly delivered by icebergs and bottom currents. Iceberg delivery was significantly controlled by factors such as water depth, proximity to the iceberg sources, and invasion of the Modified Circumpolar Deep Water. Bottom current activity was stronger in the Western Ross Sea (WRS) than in the Eastern Ross Sea (ERS), controlled by the formation and transport of Dense Shelf Water. Three major sorts of coarse fraction were identified, including the quartz-rich Iceberg Rafted Detritus (IRD) originating from West Antarctic glaciers and primarily distributed in the ERS, the mafic rocks-rich IRD from the Ferrar Group as well as the McMurdo Volcanic Group and mainly found in the WRS, and deformed silt traced back to the grounding zone of the David Glacier-Dragalski Ice Tongue system. The distribution of clay minerals is dominated by a distinct binary mixing pattern. Smectite and kaolinite are mainly present in the ERS, derived from beneath the West Antarctic Ice Sheet. Higher illite and chlorite contents were found offshore of the Southern Victoria Land, derived from the East Antarctic craton. Overall, these results demonstrate that the glaciers draining into Ross Sea from both the East and West Antarctic Ice Sheets are highly dynamical in the context of modern climate conditions, with implications for potential contribution to future sea level rise.

Three new glycosides from the stems of Eurya chinensis R. Br - Hui-Jun Liang; Qian-Ran Li; Bai-Lin Li; Chen Ni; Wei-Jie Zhang; Yu-Wen Fan; Zhuo-Yi Ao; Juan-Juan Hu; Jie Yuan; Jie-Wei Wu (Natural Product Research, 2024)

Contrasting lake changes in Tibet revealed by recent multi-modal satellite observations - Jiangjun Ran; Lin Liu; Guoqing Zhang; C.K. Shum; Jiahui Qiu; Ruigang Hu; Jianping Li; Junhuan Peng; Cheinway Hwang; Yi Luan; Yue Sun; Min Xu; et al. (Science of The Total Environment, 2024)

π-π Stacking constructing efficient charge channels for perovskite photovoltaics - Chun-Hao Chen; Fan Hu; Kai-Li Wang; Jing Chen; Tian-Yu Teng; Yi-Ran Shi; Yu Xia; Zhen-Huang Su; Xing-Yu Gao; Ilhan Yavuz; Zhao-Kui Wang; Liang-Sheng Liao (Science Bulletin, 2024)

Comammox plays a functionally important role in the nitrification of rice paddy soil with different nitrogen fertilization levels - Kai Zhang; Hui-Feng Sun; You-Cai Kang; Ran Jiang; Yan-Ren Wang; Ru-Yi Zhang; Sheng-Nan Zhang; Yang-Yang Li; Peng Li; Fan Yang; Sheng Zhou; Zhe-Xue Quan (Applied Soil Ecology, 2024)

Effects of arsenic exposure on trace element levels in the hippocampus and cortex of rats and their gender differences - Xi Yan; Jun Zhang; Junyu Li; Xinglai Zhang; Yi Wang; Xiaolu Chen; Peng Luo; Ting Hu; Xueshan Cao; Hongbin Zhuang; Xiaoxiao Tang; Fang Yao; et al. (Journal of Trace Elements in Medicine and Biology, 2023)

Effects of salinity on sulfur-dominated autotrophic denitrification microorganisms: Microbial community succession, key microorganisms and response mechanisms - Zhuo-Ran Li; Xue-Ning Zhang; Hong-Cheng Wang; Hao-Yi Cheng; Ai-Jie Wang; Yan-Qing Zhang; Chong-Wei Cui; Yi-Lu Sun (Chemical Engineering Journal, 2023)

Abnormal activation of the Wnt3a/β-catenin signaling pathway promotes the expression of T-box transcription factor 3(TBX3) and the epithelial-mesenchymal transition pathway to mediate the occurrence of adenomyosis - Mengqi Li; Ting Li; Tingting Jin; Yi Chen; Lan Cheng; Qiheng Liang; Simiao Yan; Tingting Li; Qingzhen Ran; Wanqun Chen (Molecular Biology Reports, 2023)

A long way to go: impacts of urbanization on migrants’ livelihoods and rural ecology in less industrialized regions - Zhi-qi Zhang; Ming-jing Li; Wen-jun Li; Yi-ran Wei; Yi-lu Shi (Journal of Mountain Science, 2023)

Sulfur-aided aerobic biostabilization of swine manure and sawdust mixture: Humification and carbon loss - Yang Wang; Jingwen Wang; Guorong Yi; Xuan Wu; Xiu Zhang; Xu Yang; Kuok Ho Daniel Tang; Ran Xiao; Zengqiang Zhang; Guangzhou Qu; Ronghua Li (Bioresource Technology, 2023)

Enhanced retention of surface-adsorbed atomic hydrogen through sulfidation of nano zerovalent iron for water decontamination - Guan-Nan Zhou; Jia-Qi Chen; Wen-Qiang Li; Chuan-Shu He; Li Gong; Xiao-Cheng Liu; Yi-Ran Wang; Dahong Huang; Yang Mu (Chemical Engineering Journal, 2023)

Fabrication of organic P-N aerogel towards simultaneously super thermal insulation, enhanced compressive strength, flame retardancy and smoke suppression for the rigid polyurethane foam - Ying-Ming Li; Wen-Juan Hu; Shuang-Lin Hu; Yi-Ran Li; De-Yi Wang (Chemical Engineering Journal, 2023)

Potential xylose transporters regulated by CreA improved lipid yield and furfural tolerance in oleaginous yeast Saitozyma podzolica zwy-2-3 - Yulu Ran; Qingzhuoma Yang; Jie Zeng; Fazhi Li; Yu Cao; Qingrui Xu; Dairong Qiao; Hui Xu; Yi Cao (Bioresource Technology, 2023)

Short-term effects of cold spells on hematocrit among adults in Nanjing, China: A distributed-lagged effect analysis - Bei-Jing Cheng; Tian-Lin Li; Hui Li; Ke Meng; Xing-Chen Meng; Jia Wang; Chun Wang; Lin-Sheng Yang; Xin-Yi Zhu; Ran Liu (Science of The Total Environment, 2023)

Spatial variability of arsenic fractionation in an abandoned arsenic-containing mine: Insights into soil particle sizes and quantitative mineralogical analysis - Hongzhen Ran; Zhaohui Guo; Liwen Yi; Xiyuan Xiao; Rui Xu; Zhihao Hu; Tianshuang Li (Science of The Total Environment, 2023)

Non-negligibly negative role of e-waste-derived pyrogenic carbon in the soil washing of copper and polybrominated diphenyl ethers - Yi Sun; Ying Teng; Ling Zhao; Ran Li; Wenjie Ren (Journal of Hazardous Materials, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

The AMPK-dependent inhibition of autophagy plays a crucial role in protecting photoreceptor from photooxidative injury - Yu-Lin Li; Tian-Zi Zhang; Li-Kun Han; Chang He; Yi-Ran Pan; Bin Fan; Guang-Yu Li (Journal of Photochemistry and Photobiology B: Biology, 2023)

Efficient lipid synthesis of Chlorella pyrenoidosa promoted under heavy metals from electric arc furnace slag - Qing Yu; Tian-Ji Liu; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Yu-Ran Wang; Le-Le Kang; Rui Ji; Fu-Ping Wang; Xiao-Man Wang; Bao Liu; Shuang Cai; et al. (Journal of Cleaner Production, 2023)

Design and operation insights concerning a pilot-scale S0-driven autotrophic denitrification packed-bed process - Yi-Lu Sun; Zhuo-Ran Li; Xue-Ning Zhang; Heng Dong; Zhi-Min Qian; Shan Yi; Wei-Qin Zhuang; Hao-Yi Cheng; Ai-Jie Wang (Chemical Engineering Journal, 2023)

Interspecific rootstocks improve the low-temperature resistance of bitter gourd through sucrose and nitrogen metabolism regulation - Le Liang; Huashan Lian; Huanxiu Li; Yiping Dong; Wanjia Tang; Ran Zhang; Xuemei Peng; Xiaomei Li; Yi Tang (Acta Physiologiae Plantarum, 2023)

A significant loop of lake sedimentation state links catchment eco‐surroundings and lake biogenic regime shifts - Fengwei Ran; Xiaodong Nie; Shilan Wang; Tao Xiao; Changrong Yang; Yi Liu; Lingxia Wang; Yaojun Liu; Xin Chu; Zhongwu Li (Limnology and Oceanography, 2023)
As an important destination for upstream materials and element accumulation, lake sediments hold a multitude of contextual information about climatic changes and anthropogenic disturbances. However, understanding the lake sedimentation state to link catchment pressures and biogenic regime shifts remains challenging. To address this, research was conducted on the lake sedimentation state, including the dynamics, catchment drivers, effects on biogenic regimes, and responses to typical historical events using nine sediment cores from Dongting Lake, China, a typical global priority ecoregion. Three transitions of lake sedimentation state were distinguished over the century (1937, 1968, and 1993), whereby hydrologic dynamics and land‐use changes in the watershed were the direct drivers with relative contributions of 16.30% and 14.56%, respectively. Lake sedimentation state and organic matter inputs not only preceded sediment biogenic elements at the shift time but also exhibited nonlinear trigger effects on biogenic element contents ( R 2 = 0.47, p

Source apportionment of nitrate in the Pearl River Estuary using δ15N and δ18O values and isotope mixing model - Ran Long; Fei Tian; Jian-hua Chen; Yan-bo Zhou; Xue-fei Li; Yi-tong Li; Hai-wei Tang; Hai-gang Chen (Marine Pollution Bulletin, 2023)

Enhanced removal of organic matter from oxygen-pressure leaching solution by modified anode slime - Yuhu Li; Ran Liu; Yudong Yang; Sijie Yang; Yi Zhao (Journal of Cleaner Production, 2023)

Three new constituents from the Tujia ethnomedicine Swertia punicea Hemsl. - Pan Yi; Bin Li; Salman Zafar; Sajjad Ali; Wen-Bing Sheng; Yu Mao; Fang Zhou; Wen-Ming Chen; Yan-Ran Tang; Cai-Yun Peng; M. Iqbal Choudhary; Atta-ur- Rahman; et al. (Natural Product Research, 2023)

Chemodiversity of soil organic matters determines biodegradation of polychlorinated biphenyls by a graphene oxide-assisted bacterial agent - Ran Li; Ying Teng; Yi Sun; Yongfeng Xu; Zuopeng Wang; Xia Wang; Wenbo Hu; Wenjie Ren; Ling Zhao; Yongming Luo (Journal of Hazardous Materials, 2023)

Yellow Petal locus GaYP promotes flavonol biosynthesis and yellow coloration in petals of Asiatic cotton (Gossypium arboreum) - Yaohua Li; Lingfang Ran; Tong Mo; Nian Liu; Jianyan Zeng; Aimin Liang; Chuannan Wang; Qingwei Suo; Zhong Chen; Yi Wang; Nianjuan Fang; Shijia Xu; et al. (Theoretical and Applied Genetics, 2023)

Hyperbranched polyethyleneimine-functionalised chitosan aerogel for highly efficient removal of melanoidins from wastewater - Jia-Yi Tang; Yan-Shu Xiong; Ming-Xing Li; Ran Jia; Li-Shu Zhou; Bo-Huan Fan; Kai Li; Wen Li; Hong Li; Hai-Qin Lu (Journal of Hazardous Materials, 2023)

Experiment study on seismic behavior of squat UHPC shear walls subjected to tension-shear combined cyclic load - Yue-Yi Li; Ran Ding; Jian-Guo Nie (Engineering Structures, 2023)

Two pathways drive enhanced nitrogen acquisition via a complementarity effect in long-term intercropping - Yi Xing; Rui-Peng Yu; Ran An; Ning Yang; Jin-Pu Wu; Huai-Ying Ma; Jiu-Dong Zhang; Xing-Guo Bao; Hans Lambers; Long Li (Field Crops Research, 2023)

Deep Sc-RNA sequencing decoding the molecular dynamic architecture of the human retina - Lulin Huang; Runze Li; Lin Ye; Shanshan Zhang; Huaping Tian; Mingyan Du; Chao Qu; Shujin Li; Jie Li; Mu Yang; Biao Wu; Ran Chen; et al. (Science China Life Sciences, 2023)

Enhanced bifunctional adsorption of anionic and cationic pollutants by MgAl LDH nanosheets modified montmorillonite via acid-salt activation - Xingjian Dai; Chuan Jing; Kailin Li; Xiaotian Zhang; Dan Song; Li Feng; Xiaoying Liu; Hui Ding; Haodi Ran; Kangwen Zhu; Nan Dai; Shuang Yi; et al. (Applied Clay Science, 2023)

Identification of SNPs and candidate genes associated with early growth in orange-spotted grouper (Epinephelus coioides) by a genome-wide association study - Chun Hui Ai; Zong Xian Zhu; Dan Dan Huang; Gan Yang; Tong De Liu; Ying Bai; Xue Ying Liang; Ying Ying Xiong; Yi Long Lin; Hao Ran Lin; Shui Sheng Li; Jun Hong Xia (Aquaculture, 2023)

Inconsistent patterns of Holocene rainfall changes at the East Asian monsoon margin compared to the core monsoon region - Xin Zhou; Tao Zhan; Ning Tan; Luyao Tu; John P. Smol; Shiwei Jiang; Fangming Zeng; Xiaoyan Liu; Xiangzhong Li; Guangxin Liu; Yi Liu; Ran Zhang; et al. (Quaternary Science Reviews, 2023)

Seismic performance of squat UHPC shear walls subjected to high-compression shear combined cyclic load - Yue-Yi Li; Jian-Guo Nie; Ran Ding; Jian-Sheng Fan (Engineering Structures, 2023)

Repaired surface structural imperfection of tin Wide-Bandgap perovskite films for photovoltaic application - Tian-Yu Teng; Fan Hu; Yan-Hui Lou; Jun-Jie Cao; Chun-Hao Chen; Yi-Ran Shi; Kai-Li Wang; Jing Chen; Zhao-Kui Wang; Liang-Sheng Liao (Chemical Engineering Journal, 2023)

Inkjet-printed MoS2-based 3D-structured electrocatalysts on Cu films for ultra-efficient hydrogen evolution reaction - Pei-Zhen Li; Na Chen; Ammar Al-Hamry; Evgeniya Sheremet; Ran Lu; Yi Yang; Olfa Kanoun; Reinhard R. Baumann; Raul D. Rodriguez; Jin-Ju Chen (Chemical Engineering Journal, 2023)

Simultaneous adsorption and fluorescent detection of Cr(VI) via lanthanide coordinating polymeric porous microparticles - Qimeng Ran; Zilin Fan; Xinkai Guo; Xiulan Li; Keyu Yi; Xiaobo Liu; Kun Jia (Chemical Engineering Journal, 2023)

Whole-genome sequencing and comparative genomic analysis of a pathogenic Enterocytozoon hepatopenaei strain isolated from Litopenaeus vannamei - Libao Wang; Hui Li; Wenjun Shi; Yi Qiao; Pan Wang; Zhijun Yu; Ran Zhao; Runhao Hu; Hui Shen; Jie Cheng; Ge Jiang; Xintong Huang; et al. (Aquaculture International, 2023)

Sesquiterpenoids and monoterpenoids from the water decoction of Valeriana officinalis L - Shi-Wei Li; Bian-Xia Xue; Tian-Tian Yang; Ran Li; Mingjie Zhang; Miao Wang; Li-Hua Zhang; Peng Zhang; Yi Zhang; Tao Wang; Shao-Xia Wang; Hong-Hua Wu (Phytochemistry, 2023)

Effects of soil and water conservation measures on sediment delivery processes in a hilly and gully watershed - Yi Zeng; Xiangdong Meng; Bing Wang; Mengjie Li; Dan Chen; Lishan Ran; Nufang Fang; Lingshan Ni; Zhihua Shi (Journal of Hydrology, 2023)

Efficient electrocatalytic reduction of CO2 to CO on highly dispersed Ag nanoparticles confined by Poly(ionic liquid) - Guo-Yi Duan; Xiao-Qiang Li; Yi-Ran Du; Bao-Hua Xu (Chemical Engineering Journal, 2023)

Andrographolide ameliorates hepatic steatosis by suppressing FATP2-mediated fatty acid uptake in mice with nonalcoholic fatty liver disease - Li-Sha Ran; Ya-Zeng Wu; Yi-Wen Gan; Hong-Lian Wang; Li-Juan Wu; Chun-Mei Zheng; Yao Ming; Ran Xiong; Yong-Lin Li; Shi-Hang Lei; Xue Wang; Xiao-Qing Lao; et al. (Journal of Natural Medicines, 2023)
Excessive intrahepatocellular lipid accumulation or steatosis is caused by abnormal lipid metabolism and a common character of nonalcoholic fatty liver disease (NAFLD), which may progress into cirrhosis and hepatocellular cancer. Andrographolide (Andro) is the primary active ingredient extracted from Andrographis paniculata , showing a protective role against dietary steatosis with the mechanism not fully understood. In this study, we showed that administration of Andro (50, 100, and 200 mg/kg/day for 8 weeks, respectively) attenuated obesity and metabolic syndrome in high-fat diet (HFD)-fed mice with improved glucose tolerance, insulin sensitivity, and reduced hyperinsulinemia, hyperglycemia, and hyperlipidemia. HFD-fed mice presented hepatic steatosis, which was significantly prevented by Andro. In vitro, Andro decreased the intracellular lipid droplets in oleic acid-treated LO2 cells. The selected RT-PCR array revealed a robust expression suppression of the fatty acid transport proteins (FATPs) by Andro treatment. Most importantly, we found that Andro consistently reduced the expression of FATP2 in both the oleic acid-treated LO2 cells and liver tissues of HFD-fed mice. Overexpression of FATP2 abolished the lipid-lowering effect of Andro in oleic acid-treated LO2 cells. Andro treatment also reduced the fatty acid uptake in oleic acid-treated LO2 cells, which was blunted by FATP2 overexpression. Collectively, our findings reveal a novel mechanism underlying the anti-steatosis effect of Andro by suppressing FATP2-mediated fatty acid uptake, suggesting the potential therapeutic application of Andro in the treatment of NAFLD. Graphical abstract

Intercropping affects the physiology and cadmium absorption of pakchoi, lettuce, and radish seedlings - Le Liang; Xiaomei Li; Huanxiu Li; Xuemei Peng; Ran Zhang; Wanjia Tang; Yiping Dong; Yi Tang (Environmental Science and Pollution Research, 2023)

The roles of ETS transcription factors in liver fibrosis - Li-Ye Zhang; Yong Tan; Xiao-Jie Luo; Jiang-Feng Wu; Yi-Ran Ni (Human Cell, 2022)

Paenibacillus hamazuiensis sp. nov., a bacterium isolated from Hamazui hot spring in Yunnan province, south-west China - Juan Wang; Ming Deng; En-Min Zhou; Lei Ran; Cui-Ping Miao; Yi-Qing Li; Jun-Mei Ding; Shu-Kun Tang (Archives of Microbiology, 2022)

Flowering characteristics and mating system of Fritillaria cirrhosa (Liliaceae), an endangered plant in China - Yanzhu Ma; Zhijia Cui; Chun Ya Cheng; Ran Li; Haixu Wu; Ling Jin; Yi Ma; Zhenheng Wang (Brazilian Journal of Botany, 2022)

New polymerized sesquiterpene lactones from Ainsliaea yunnanensis and their activity evaluation - Na Zhou; Jin-Jie Li; Yong Wu; Ze-Yu Wang; Xin Wang; Zhi-Peng Yin; Xin-Peng Wang; Yi-Ran Liu; Xiao-Ya Shang (Natural Product Research, 2022)

Mycotoxin surveillance on wheats in Shandong province, China, reveals non-negligible probabilistic health risk of chronic gastrointestinal diseases posed by deoxynivalenol - Fenghua Li; Xinglan Duan; Liwen Zhang; Dafeng Jiang; Xianqi Zhao; En Meng; Ran Yi; Chang Liu; Yirui Li; Jia-Sheng Wang; Xiulan Zhao; Wei Li; et al. (Environmental Science and Pollution Research, 2022)

Apportioning above- and below-ground effects of moss biocrusts on soil detachment by overland flow in a subtropical climate - Guan-hua Zhang; Liang Yi; Wen-feng Ding; Xu Lei; Yi-ran Wang; Bao-yang Sun; Jian-ming Li (Journal of Mountain Science, 2021)

The relationship between diabetes-related cognitive dysfunction and leukoaraiosis - Chun-lan Yuan; Ran Yi; Qi Dong; Li-fen Yao; Bin Liu (Acta Neurologica Belgica, 2021)

A new indole alkaloid with HUVEC proliferation activities from Nauclea officinalis - Shi-Ying Mai; Yong-Hui Li; Xu-Guang Zhang; Yi-Ran Wang; Jun-Qing Zhang; An Jia (Natural Product Research, 2021)

The effect of consecutive ambient air pollution on the hospital admission from chronic obstructive pulmonary disease in the Chengdu region, China - Yi Zhang; Ziyue Wang; Yu Cao; Lifu Zhang; Guan Wang; Fangjie Dong; Ren Deng; Baogen Guo; Li Zeng; Peng Wang; Ruimei Dai; Yu Ran; et al. (Air Quality, Atmosphere & Health, 2021)

KCNQ Channels in the Mesolimbic Reward Circuit Regulate Nociception in Chronic Pain in Mice - Hao-Ran Wang; Su-Wan Hu; Song Zhang; Yu Song; Xiao-Yi Wang; Lei Wang; Yang-Yang Li; Yu-Mei Yu; He Liu; Di Liu; Hai-Lei Ding; Jun-Li Cao (Neuroscience Bulletin, 2021)
Mesocorticolimbic dopaminergic (DA) neurons have been implicated in regulating nociception in chronic pain, yet the mechanisms are barely understood. Here, we found that chronic constructive injury (CCI) in mice increased the firing activity and decreased the KCNQ channel-mediated M-currents in ventral tegmental area (VTA) DA neurons projecting to the nucleus accumbens (NAc). Chemogenetic inhibition of the VTA-to-NAc DA neurons alleviated CCI-induced thermal nociception. Opposite changes in the firing activity and M-currents were recorded in VTA DA neurons projecting to the medial prefrontal cortex (mPFC) but did not affect nociception. In addition, intra-VTA injection of retigabine, a KCNQ opener, while reversing the changes of the VTA-to-NAc DA neurons, alleviated CCI-induced nociception, and this was abolished by injecting exogenous BDNF into the NAc. Taken together, these findings highlight a vital role of KCNQ channel-mediated modulation of mesolimbic DA activity in regulating thermal nociception in the chronic pain state.

Effects of Co-Applications of Biochar and Solid Digestate on Enzyme Activities and Heavy Metals Bioavailability in Cd-Polluted Greenhouse Soil - Shuaixing Xue; Fengfen Chen; Yuying Wang; Zhijiang Shao; Congguang Zhang; Ling Qiu; Yi Ran; Li He (Water, Air, & Soil Pollution, 2021)

Effects of Shallow Water Table Depth on Vegetative Filter Strips Retarding Transport of Nonpoint Source Pollution in Controlled Flume Experiments - Ran Li; Yi-Ming Kuo (International Journal of Environmental Research, 2021)

Aberration of Serum and Tissue N-Glycans in Mouse β1,4-GalT1 Y286L Mutant Variants - Ran Cao; Tian-Chan Zhang; Ya-Ran Chen; Cui Cao; Huan Chen; Yi-Fan Huang; Morihisa Fujita; Li Liu; Josef Voglmeir (Glycoconjugate Journal, 2020)

A threshold stresses-based permeability variation model for microcracked porous rocks - Xing Li; Yi-Feng Chen; Kai Wei; Ran Hu; Zhi-Bing Yang (European Journal of Environmental and Civil Engineering, 2020)

Epitranscriptomic technologies and analyses - Xiaoyu Li; Qiao-Xia Liang; Jin-Ran Lin; Jinying Peng; Jian-Hua Yang; Chengqi Yi; Yang Yu; Qiangfeng Cliff Zhang; Ke-Ren Zhou (Science China Life Sciences, 2020)

Juxtaposed membranes underpin cellular adhesion and display unilateral cell division of multicellular magnetotactic prokaryotes - Xin‐Xin Qian; Claire‐Lise Santini; Artemis Kosta; Nicolas Menguy; Hugo Le Guenno; Wenyan Zhang; Jinhua Li; Yi‐Ran Chen; Jia Liu; François Alberto; Leon Espinosa; Tian Xiao; et al. (Environmental Microbiology, 2020)
Summary Multicellular magnetotactic prokaryotes (MMPs) exhibit peculiar coordination of swimming along geomagnetic field lines. Approximately 40–80 cells assemble, with a helical geometry or axisymmetry, into spherical or ellipsoidal MMPs respectively. To contribute to a comprehensive understanding of bacterial multicellularity here we took multiple microscopic approaches to study the diversity, assembly, reproduction and motility of ellipsoidal MMPs. Using correlative fluorescence in situ hybridization and scanning electron microscopy analysis, we found an unexpected diversity in populations of ellipsoidal MMPs in the Mediterranean Sea. The high‐pressure freezing/freeze substitution fixation technique allowed us to show, for the first time, that cells adhere via juxtaposed membranes and are held together by a rimming lattice. Fluorescence confocal microscopy and ultrathin section images revealed not only the one‐layer hollow three‐dimensional architecture, but also periphery–core unilateral constriction of constituent cells and unidirectional binary fission of the ellipsoidal MMPs. This finding suggests the evolution toward MMPs multicellularity via the mechanism of incomplete separation of offspring. Remarkably, thousands of flagellar at the periphery surface of cells underpin the coordinated swimming of MMPs in response to mechanical, chemical, magnetic and optical stimuli, including a magnetotactic photokinesis behaviour. Together these results unveil the unique structure and function property of ellipsoidal MMPs.

Association of Corticotropin-Releasing Hormone Receptor-1 Gene Polymorphisms and Personality Traits with Violent Aggression in Male Adolescents - Li Liu; Yi Qiao; Yang Shao; Shun-ying Yu; Chen Zhang; Ran Zhang; Dong-xiang Wang; Min Zhao; Bin Xie (Journal of Molecular Neuroscience, 2020)

De Novo and Inherited SETD1A Variants in Early-onset Epilepsy - Xiuya Yu; Lin Yang; Jin Li; Wanxing Li; Dongzhi Li; Ran Wang; Kai Wu; Wenhao Chen; Yi Zhang; Zilong Qiu; Wenhao Zhou (Neuroscience Bulletin, 2019)

Toxicity, residue, degradation and detection methods of the insecticide triazophos - Fang-Wei Yang; Yi-Xuan Li; Fa-Zheng Ren; Ran Wang; Guo-Fang Pang (Environmental Chemistry Letters, 2019)

Antagonistic activity and protective effect of a Bacillus subtilis isolate against fish pathogen Edwardsiella piscicida - Xiaomeng Ren; Binbin Wu; Feng Zhao; Lingling Qi; Xianfeng Qiu; Ran Li; Sisi Yang; Fuguo Liu; Ganfeng Yi; Xuezhi Ding; Liqiu Xia; Yunjun Sun (Fisheries Science, 2019)

Experimental investigation on the mechanical characteristics of gas-bearing coal considering the impact of moisture - Ming-yi Chen; Yuan-ping Cheng; Jing-chun Wang; Hao-ran Li; Ning Wang (Arabian Journal of Geosciences, 2019)

Recovery of unstable digestion of vegetable waste by adding trace elements using the bicarbonate alkalinity to total alkalinity ratio as an early warning indicator - Dong Li; Juan Sun; Qin Cao; Yichao Chen; Xiaofeng Liu; Yi Ran (Biodegradation, 2019)

Identification and detection sensitivity of Microcystis aeruginosa from mixed and field samples using MALDI-TOF MS - Li-Wei Sun; Wen-Jing Jiang; Jun-Yi Zhang; Wen-Qian Wang; Yang Du; Hiroaki Sato; Masanobu Kawachi; Ran Yu (Environmental Monitoring and Assessment, 2018)

Using generalized additive models to investigate factors influencing cyanobacterial abundance through phycocyanin fluorescence in East Lake, China - Yi-Ming Kuo; Jun Yang; Wen-wen Liu; Enmin Zhao; Ran Li; Liquan Yao (Environmental Monitoring and Assessment, 2018)

Effects of wind–wave disturbances on adsorption and desorption of tetracycline and sulfadimidine in water–sediment systems - Qianjiahua Liao; Zheng Huang; Shu Li; Yi Wang; Yuqing Liu; Ran Luo; Jingge Shang (Environmental Science and Pollution Research, 2018)

Potential health risk assessment through ingestion and dermal contact arsenic-contaminated groundwater in Jianghan Plain, China - Ran Li; Yi-Ming Kuo; Wen-wen Liu; Cheng-Shin Jang; Enmin Zhao; Liquan Yao (Environmental Geochemistry and Health, 2018)

Genetic mapping and salt tolerance of a novel D1-allelic mutant of rice (Oryza sativa L.) - Wei-jiang Tian; Xiao-qiong Zhang; Xiao-wen Wang; Jia Xie; Yang-yang Li; Ying Sun; Yi-ran Tao; Yu-zhen Xiong; Xian-chun Sang (Acta Physiologiae Plantarum, 2018)

The mitochondrial genome of red-necked phalarope Phalaropus lobatus (Charadriiformes: Scolopacidae) and phylogeny analysis among Scolopacidae - Wei Liu; Chaochao Hu; Wenli Xie; Peng Chen; Yi Zhang; Ran Yao; Kexin Li; Qing Chang (Genes & Genomics, 2018)

Effects of indole-3-butytric acid on lead and zinc accumulations in Pseudostellaria maximowicziana - Zhi Ran; Cheng Chen; Fabo Chen; Ming’an Liao; Lijin Lin; Xiulan Lv; Qunxian Deng; Xun Wang; Jin Wang; Yi Tang; Huaxiong Li (Environmental Monitoring and Assessment, 2018)

Long-term agronomic practices alter the composition of asymbiotic diazotrophic bacterial community and their nitrogen fixation genes in an acidic red soil - Weibing Xun; Wei Li; Ting Huang; Yi Ren; Wu Xiong; Youzhi Miao; Wei Ran; Dongchu Li; Qirong Shen; Ruifu Zhang (Biology and Fertility of Soils, 2018)

L1CAM drives oncogenicity in esophageal squamous cell carcinoma by stimulation of ezrin transcription - Jin-Cheng Guo; Yang-Min Xie; Li-Qiang Ran; Hui-Hui Cao; Chun Sun; Jian-Yi Wu; Zhi-Yong Wu; Lian-Di Liao; Wei-Jiang Zhao; Wang-Kai Fang; En-Min Li; Li-Yan Xu; et al. (Journal of Molecular Medicine, 2017)

A novel missense mutation of $$ADAR1$$ ADAR 1 gene in a Chinese family leading to dyschromatosis symmetrica hereditaria and literature review - Shuai-Mei Liu; Meng-Xia Ni; Ming-Chao Zhang; Pei-Ran Zhu; Qiu-Yu Wu; Wei-Jun Jiang; Jing Zhang; Wei-Wei Li; Xin-Yi Xia (Journal of Genetics, 2017)

The Effect of Selenium on the Cd-Induced Apoptosis via NO-Mediated Mitochondrial Apoptosis Pathway in Chicken Liver - Runxiang Zhang; Ran Yi; Yanju Bi; Lu Xing; Jun Bao; Jianhong Li (Biological Trace Element Research, 2017)

Trans-ethnic fine-mapping of genetic loci for body mass index in the diverse ancestral populations of the Population Architecture using Genomics and Epidemiology (PAGE) Study reveals evidence for multiple signals at established loci - Lindsay Fernández-Rhodes; Jian Gong; Jeffrey Haessler; Nora Franceschini; Mariaelisa Graff; Katherine K. Nishimura; Yujie Wang; Heather M. Highland; Sachiko Yoneyama; William S. Bush; Robert Goodloe; Marylyn D. Ritchie; et al. (Human Genetics, 2017)

Comparative proteomic analysis of apple branches susceptible and resistant to ring rot disease - Zhang Cai-xia; Tian Yi; Zhang Li-yi; Zong Ze-ran; Cong Pei-hua (European Journal of Plant Pathology, 2017)

miR-143 regulates proliferation and differentiation of bovine skeletal muscle satellite cells by targeting IGFBP5 - Wei Ran Zhang; Hui Na Zhang; Yi Min Wang; Yang Dai; Xin Feng Liu; Xin Li; Xiang Bin Ding; Hong Guo (In Vitro Cellular & Developmental Biology - Animal, 2017)

Isolation, Characterization, and Bioinformatic Analyses of Lytic Salmonella Enteritidis Phages and Tests of Their Antibacterial Activity in Food - Han Han; Xiaoting Wei; Yi Wei; Xiufeng Zhang; Xuemin Li; Jinzhong Jiang; Ran Wang (Current Microbiology, 2017)

Characterization of Collagen Enzymatic Hydrolysates Derived from Lizardfish ( Synodus fuscus ) Scales - Junde Chen; Ying Liu; Ruizao Yi; Long Li; Ran Gao; Nuohua Xu; Meihua Zheng (Journal of Aquatic Food Product Technology, 2017)

Complete genome sequence and comparative genome analysis of a new special Yersinia enterocolitica - Guoxiang Shi; Mingming Su; Junrong Liang; Ran Duan; Wenpeng Gu; Yuchun Xiao; Zhewen Zhang; Haiyan Qiu; Zheng Zhang; Yi Li; Xiaohe Zhang; Yunchao Ling; et al. (Archives of Microbiology, 2016)

Evolution of the microbial community of the biofilm in a methane-based membrane biofilm reactor reducing multiple electron acceptors - Ran Chen; Yi-Hao Luo; Jia-Xian Chen; Yin Zhang; Li-Lian Wen; Ling-Dong Shi; Youneng Tang; Bruce E. Rittmann; Ping Zheng; He-Ping Zhao (Environmental Science and Pollution Research, 2016)

Ectomycorrhizae of Tuber huidongense and T. liyuanum with Castanea mollissima and Pinus armandii - Shan-Ping Wan; Fu-Qiang Yu; Li Tang; Ran Wang; Yun Wang; Pei-Gui Liu; Xiang-Hua Wang; Yi Zheng (Mycorrhiza, 2016)

Evaluation of Groundwater Leakage into a Drainage Tunnel in Jinping-I Arch Dam Foundation in Southwestern China: A Case Study - Yi-Feng Chen; Jia-Min Hong; Hua-Kang Zheng; Yi Li; Ran Hu; Chuang-Bing Zhou (Rock Mechanics and Rock Engineering, 2016)

microRNA-128 regulates the proliferation and differentiation of bovine skeletal muscle satellite cells by repressing Sp1 - Yang Dai; Wei Ran Zhang; Yi Min Wang; Xin Feng Liu; Xin Li; Xiang Bin Ding; Hong Guo (Molecular and Cellular Biochemistry, 2016)

The role of microRNA-1 and microRNA-206 in the proliferation and differentiation of bovine skeletal muscle satellite cells - Yang Dai; Yi Min Wang; Wei Ran Zhang; Xin Feng Liu; Xin Li; Xiang Bin Ding; Hong Guo (In Vitro Cellular & Developmental Biology - Animal, 2016)

PPR protein PDM1/SEL1 is involved in RNA editing and splicing of plastid genes in Arabidopsis thaliana - Hong-Dao Zhang; Yong-Lan Cui; Chao Huang; Qian-Qian Yin; Xue-Mei Qin; Te Xu; Xiao-Fang He; Yi Zhang; Zi-Ran Li; Zhong-Nan Yang (Photosynthesis Research, 2015)

Enhanced hydroxyl radical generation in the combined ozonation and electrolysis process using carbon nanotubes containing gas diffusion cathode - Donghai Wu; Guanghua Lu; Ran Zhang; Qiuhong Lin; Zhenhua Yan; Jianchao Liu; Yi Li (Environmental Science and Pollution Research, 2015)

A novel species of ellipsoidal multicellular magnetotactic prokaryotes from L ake Y uehu in C hina - Yi‐Ran Chen; Rui Zhang; Hai‐Jian Du; Hong‐Miao Pan; Wen‐Yan Zhang; Ke Zhou; Jin‐Hua Li; Tian Xiao; Long‐Fei Wu (Environmental Microbiology, 2015)
Summary Two morphotypes of multicellular magnetotactic prokaryotes ( MMPs ) have been identified: spherical (several species) and ellipsoidal (previously one species). Here, we report novel ellipsoidal MMPs that are ∼ 10 × 8 μm in size, and composed of about 86 cells arranged in six to eight interlaced circles. Each MMP was composed of cells that synthesized either bullet‐shaped magnetite magnetosomes alone, or both bullet‐shaped magnetite and rectangular greigite magnetosomes. They showed north‐seeking magnetotaxis, ping‐pong motility and negative phototaxis at a velocity up to 300 μm s −1 . During reproduction, they divided along either their long‐ or short‐body axes. For genetic analysis, we sorted the ellipsoidal MMPs with micromanipulation and amplified their genomes using multiple displacement amplification. We sequenced the 16 S r RNA gene and found 6.9% sequence divergence from that of ellipsoidal MMPs , Candidatus Magnetananas tsingtaoensis and > 8.3% divergence from those of spherical MMPs . Therefore, the novel MMPs belong to different species and genus compared with the currently known ellipsoidal and spherical MMPs respectively. The novel MMPs display a morphological cell differentiation, implying a potential division of labour. These findings provide new insights into the diversity of MMPs in general, and contribute to our understanding of the evolution of multicellularity among prokaryotes.

Determination of royal jelly freshness by ELISA with a highly specific anti-apalbumin 1, major royal jelly protein 1 antibody - Li-rong Shen; Yi-ran Wang; Liang Zhai; Wen-xiu Zhou; Liang-liang Tan; Mei-lu Li; Dan-dan Liu; Fa Xiao (Journal of Zhejiang University-SCIENCE B, 2015)

Lipopolysaccharides Reduce Adipogenesis in 3T3-L1 Adipocytes Through Activation of NF-κB Pathway and Downregulation of AMPK Expression - Lifeng Wang; Linlin Li; Xinjian Ran; Mei Long; Minfang Zhang; Yicun Tao; Xin Luo; Ye Wang; Yi Jiao; Xinmin Mao; Jun Ren (Cardiovascular Toxicology, 2013)

The Antitumor Effect of a New Docetaxel-Loaded Microbubble Combined with Low-Frequency Ultrasound In Vitro: Preparation and Parameter Analysis - Shu-Ting Ren; Yi-Ran Liao; Xiao-Ning Kang; Yi-Ping Li; Hui Zhang; Hong Ai; Qiang Sun; Jing Jing; Xing-Hua Zhao; Li-Fang Tan; Xin-Liang Shen; Bing Wang (Pharmaceutical Research, 2013)

Mitochondrial Dysfunction Induced by Honokiol - Jia-Xin Dong; Guang-Yuan Zhao; Qiu-Li-Yang Yu; Ran Li; Lian Yuan; Jing Chen; Yi Liu (The Journal of Membrane Biology, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Toxicity of CdTe QDs with different sizes targeted to HSA investigated by two electrochemical methods - Zi-Qiang Xu; Lu Lai; Dong-Wei Li; Ran Li; Chen Xiang; Feng-Lei Jiang; Shao-Fa Sun; Yi Liu (Molecular Biology Reports, 2013)

Abundance and composition of ammonia-oxidizing bacteria and archaea in different types of soil in the Yangtze River estuary - Xiao-ran Li; Yi-ping Xiao; Wen-wei Ren; Zeng-fu Liu; Jin-huan Shi; Zhe-xue Quan (Journal of Zhejiang University-SCIENCE B, 2012)

Individual and combined effects of MDM2 SNP309 and TP53 Arg72Pro on breast cancer risk: an updated meta-analysis - Hongtao Cheng; Biao Ma; Ran Jiang; Wei Wang; Hui Guo; Na Shen; Dapeng Li; Qunzi Zhao; Rui Wang; Pengfei Yi; Yue Zhao; Zeming Liu; et al. (Molecular Biology Reports, 2012)

Magnetic field can alleviate toxicological effect induced by cadmium in mungbean seedlings - Yi-ping Chen; Ran Li; Jun-Min He (Ecotoxicology, 2011)

Microcalorimetric Study on the Effect of Ce3+ on Halobacterium halobium R1 - Yi Liu; Jun Yin; Ran Li; Li Li; Jie Dai; Ye-Zhong Zhang; Ping Shen (Biological Trace Element Research, 2008)

Effect of different dietary raw to pre-gelatinized starch ratios on growth performance, feed utilization and body composition of juvenile yellowfin seabream (Sparus latus) - Xiao-Yi Wu; Yong-Jian Liu; Li-Xia Tian; Kang-Sen Mai; Ran Guo; Sheng-Jie Jin (Aquaculture International, 2007)